Molecular Imaging of the Translocator Protein (TSPO) in a Pre-Clinical Model of Breast Cancer - Wyatt, Shelby K. (Mol Imaging Biol, 2009)
PURPOSE: To quantitatively evaluate the utility of a translocator protein (TSPO)-targeted near-infrared (NIR) probe (NIR-conPK11195) for in vivo molecular imaging of TSPO in breast cancer. PROCEDURES: NIR-conPK11195 uptake and TSPO-specificity were validated in TSPO-expressing human breast adenocarcinoma cells (MDA-MB-231). In vivo NIR-conPK11195 biodistribution and accumulation were quantitatively evaluated in athymic nude mice bearing MDA-MB-231 xenografts. RESULTS: Fluorescence micrographs illustrated intracellular labeling of MDA-MB-231 cells by NIR-conPK11195. Quantitative uptake and competition assays demonstrated dose-dependent (p<0.001) and TSPO-specific (p<0.001) NIR-conPK11195 uptake. In vivo, NIR-conPK11195 preferentially labeled MDA-MB-231 tumors with an 11-fold (p<0.001) and 7-fold (p<0.001) contrast enhancement over normal tissue and unconjugated NIR dye, respectively. CONCLUSIONS: NIR-conPK11195 appears to be a promising TSPO-targeted molecular imaging agent for visualization and quantification of breast cancer cells in vivo. This research represents the first study to demonstrate the feasibility of TSPO imaging as an alternative breast cancer imaging approach.